Chemical priming of plant defense responses to pathogen attacks - Hönig, Martin; Roeber, Venja M.; Schmülling, Thomas; Cortleven, Anne (Frontiers in Plant Science, 2023)
Plants can acquire an improved resistance against pathogen attacks by exogenous application of natural or artificial compounds. In a process called chemical priming, application of these compounds causes earlier, faster and/or stronger responses to pathogen attacks. The primed defense may persist over a stress-free time (lag phase) and may be expressed also in plant organs that have not been directly treated with the compound. This review summarizes the current knowledge on the signaling pathways involved in chemical priming of plant defense responses to pathogen attacks. Chemical priming in induced systemic resistance (ISR) and systemic acquired resistance (SAR) is highlighted. The roles of the transcriptional coactivator NONEXPRESSOR OF PR1 (NPR1), a key regulator of plant immunity, induced resistance (IR) and salicylic acid signaling during chemical priming are underlined. Finally, we consider the potential usage of chemical priming to enhance plant resistance to pathogens in agriculture.